Pathophysiology and natural based therapeutic strategies for psoriasis: Insights from promising clinical trials - Praveen, Asma; Sharma, Ajay (Journal of Neonatal Surgery, 2025)
Psoriasis is a long-term autoimmune inflammatory ailment with a multifaceted pathophysiology altered by genetic tendency, environmental triggers, and immune system abnormalities. It is marked by excessive keratinocyte growth, immune dysfunction, and increased oxidative stress, contributing to persistent inflammation. Conventional therapies, including corticosteroids, immunosuppressants, and biologics, have limitations due to adverse effects and long-term safety concerns. This review explores the pathogenesis of psoriasis, highlighting immune response mechanisms, oxidative stress involvement, and the potential of natural compounds as therapeutic alternatives. Medicinal plants, phytochemicals, and biologically active components such as flavonoids, polyphenols, and alkaloids have revealed promising anti-inflammatory and immunomodulatory effects. Clinical studies suggest that these natural agents can regulate cytokine production, inhibit keratinocyte proliferation, and modulate oxidative stress pathways, offering a safer and more profitable approach to psoriasis controlling. This review further explores the molecular interactions between plant-based bioactive agents and immune mechanisms, paving the way for novel natural therapeutic strategies